Overview of a multi-stakeholder dialogue around Shared Services for Health: the Digital Health Opportunity in Bangladesh. Issue 1 (December 2015) - Ashraf, Sania; Moore, Carolyn; Gupta, Vaibhav; Chowdhury, Anir; Azad, Abul; Singh, Neelu; Hagan, David; Labrique, Alain
Abstract Background National level policymaking and implementation includes multiple stakeholders with varied interests and priorities. Multi-stakeholder dialogues (MSDs) can facilitate consensus building through collective identification of challenges, recognition of shared goals and interests, and creation of solution pathways. This can shape joint planning and implementation for long-term efficiency in health and other sectors. Scaling up the effective use of information and communication technologies (ICTs) requires cohesive strategic planning towards a shared goal. In Bangladesh, the government and partners convened an MSD in March 2015 to increase stakeholder engagement in policymaking and implementation of a national ICT or electronic or mobile health (eHealth or mHealth) strategy, which seeks to incorporate ICTs into the national health system, aligning with the Digital Bangladesh Vision 2021. Methods Relevant stakeholders were identified and key priorities and challenges were mapped through key informant interviews. An MSD was conducted with key stakeholders in Dhaka, Bangladesh. The MSD included presentations, group option generation, agreement and prioritization of barriers to scaling up ICTs. Results The MSD approach to building consensus on key priorities highlights the value of dialogue and collaboration with relevant stakeholders to encourage country ownership of nationwide efforts such as ICT scale-up. This MSD showed the dynamic context in which stakeholders operate, including those from academia, donors and foundations, healthcare professionals, associations, multilateral organizations, non-governmental organizations, partner countries and the private sector. Through this MSD, participants improved understanding of each other's contributions and interests, identified existing relationships, and agreed on policy and implementation gaps that needed to be filled. Collaboration among stakeholders in ICT efforts and research can promote a cohesive approach to scaling up, as well as improve policymaking by integrating interests and feedback of different key cross sectoral actors. Conclusion MSDs can align stakeholders to identify challenges and solution pathways, and lead to coordinated action and accountability for resources and results. In addition, the MSD template and approach has been useful to guide ICT scale up in Bangladesh and could be replicated in other contexts to facilitate multi-constituency, multi-sector collaboration.